FRI0474 International Classification of Functioning, Disability, and Health (ICF) Core Sets for Connective Tissue Disease Interstitial Lung Disease (CTD-ILD) and Idiopathic Pulmonary Fibrosis (IPF) – A Necessary Map to Health Care Provision in the ERA of ICD-11. (9th June 2015) - Saketkoo, L.A.; Escorpizo, R.; Keen, K.J.; Fligelstone, K.; Birring, S.S.; Lammi, M.R.; Lasky, J.A.; LeSage, D.R.; Renzoni, E.; Russell, A.M.; Sarver, C.; Scholand, M.B.; et al.
Abstract : Background: A recent consensus project (Saketkoo et al, Thorax 2014) recommended a minimum core set of outcome measures for use in future clinical trials of CTD-ILD and IPF. The World Health Organization (WHO) introduced the International Classification of Functioning, Disability, and Health (ICF) as a scientific method of disability data collection and a universal framework of >1200 categories describing disability in terms of the bio-psycho-social model with consideration of environmental and personal factors. For accurate representation of disease, ease of healthcare provision and fair allocation of resources, it is essential that ICF Core Sets be established for rare and complex diseases. Methods: Per updated ICF linkage rules, each instrument from the published CTD-ILD and IPF core sets were deconstructed to meaningful concepts and independently linked by 2 health professionals experienced in ICF linkage (RE, LAS). Inter-linker agreement on independent linkages was analyzed (KK). A 3rd linker (OD) arbitrated if irreconcilable linkages occurred. Results: Eighty-two ICF categories were identified under the 4 ICF domains for 6 patient questionnaires and 3 traditional objective measures. The proportion of agreement ranged from 0.79 (95% CI: 0.62, 0.91) to 0.93 (0.76, 0.99) (Table 1 ) with the overall proportion of inter-linker agreement 0.86 (0.82, 0.89). 20 new "Personal Factors" and 7 suggested modifications were generated to capture important disease-specific qualities not elsewhere described in ICF, e.g. "pf_embarrassed by cough"; "pf_panic/afraid when can't get breath"; pf_fear of hurting self by overexertion; d4508_walking pace or b469_bouts of coughing to describe paroxysmal coughing spells that are often disabling in this condition. Conclusions: This is the first effort to map CTD-ILD and IPF outcome measures to the ICF. ICF Core Sets provide stream-lined disease-specific coding of disability data that support global, regional and personal health-related parity across cultures, age and socioeconomic status; enabling fair assessment of disability for policy-making, service provision, funding and rural/urban infrastructural modifications. Validation steps are planned for item analysis and potential development of a single composite instrument for clinical trials and clinical practice. The availability of ICF Core Sets in CTD-ILD and IPF will afford clinicians a smoother transition to ICD-11 which is under development and will meld diagnostic coding with the ICF. Disclosure of Interest: L. A. Saketkoo Grant/research support from: ACR/EULAR Exchange Awardee, R. Escorpizo: None declared, K. Keen: None declared, K. Fligelstone: None declared, S. Birring: None declared, M. Lammi: None declared, J. Lasky: None declared, D. LeSage: None declared, E. Renzoni: None declared, A. M. Russell: None declared, C. Sarver: None declared, M. B. Scholand: None declared, J. Varga: None declared, O. Distler: None declared